Doctoral Dissertations on China: A Bibliography of Studies in Western Languages, 1945-1970. Compilado y edit. por Leonard H. D. Gordon y Frank Y. Shulman. - Botton Beja, Flora (Estudios de Asia y África, 1977)
-